Nutritional Status of Salaried Bank Workers in Kampala, Uganda - Suubi, Rebecca; Mulira, James; Lawoko, Stephen (International Journal of Medical Research and Public Health, 2018)
Overweight and Obesity has gradually increased over the past decades globally. Studies on riskfactors for overweight and obesity have focused on general populations and patient samples. Considerably less is known on this issue among salaried workers particularly in low income countries. This study established the prevalence and social demographic, nutritional and lifestyle risk factors of overweight and obesity in a sample of bank employees in Uganda. Methodology: A cross-sectional study was conducted among 185 randomly selected salaried workers of a bank in Kampala in January 2018. Information from a questionnaire adapted from the WHO-STEPwise instrument- Nutrition Dietary patterns, physical activity, stress management coping, alcohol intake, pertinent socialdemographic information, as well as their Body Mass Index was collected and analyzed using chi-square tests and binary logistic regression the Statistical Package for Social Sciences (SPSS). Results: The overall prevalence of overweight and obesity was 51.9% (40% overweight and 11.9% obese). The likelihood of being overweight/obese was lower among; Catholics (OR= 0.262, 95%C.I= 0.088-0.779, Pvalue= 0.016) when contrasted with Anglicans, table wine drinkers (OR= 0.151, 95%C.I= 0.026-0.869, P-value = 0.034) in contrast with liquor consumers, and employees using exercise as a stress coping mechanism (OR=0.239, 95%C.I=0.086-0.661, p-value=0.006) than those using reclining as a coping mechanism. Conclusion: Overweight or obesity may be of epidemic proportion among bank workers. The identified risk factors imply that interventions targeting the management of overweight and obesity should integrate physical activity for stress management as part of the organizational Occupational Safety Strategy Package and provide remedies to control alcohol consumption. Additionally, further research to understand religious inequalities in overweight/obesity is warranted.
Keywords: Nutritional Status; Bank employees; Stress; Risk-factors; Uganda